ID COVID-19 map: the spreading cases in Surabaya, Indonesia / Awandhana Anggi Arrizki ... [et al.] - Arrizki, Awandhana Anggi; Dharmawan, Bintang; Saden, Joan Raymond Christian; Asyraf, Syed Mohd; Abdul Rasam, Abdul Rauf (College of Built Environment, 2023)
Covid-19 is one of the virus that recently occurred until now all around the world. People are really easy to get infected even just from a small contact from the sufferers.